Economic Duality in Tourist Areas: The Impact of Geographical Conditions on the Income Levels of Tourism and Non-Tourism Business Owners in Sajen Village, Pacet District - FIDYA FEBRIYANTI; NADIA MA'RUFAH AURA AISYAH; INEZ MARTA JOANA; INTAN NURAINI; INDRI KUSUMAWATI; ANNISA DAMAYANTI; NURUL HASANAH (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study seeks to examine the phenomenon of economic duality and the impact of geographical and environmental factors on the income levels of tourism and non-tourism business owners in Sajen Village, Pacet District. Employing a quantitative approach, the research utilizes primary data gathered via questionnaires, observations, interviews, and documentation. The population comprises all business actors in Sajen Village, with the sample selected through purposive sampling, targeting owners of tourism and non-tourism enterprises in areas exhibiting diverse geographical features. Data analysis involved descriptive and explanatory methods to discern income distribution patterns and assess the effects of geographical elements, such as accessibility, proximity to tourist sites, and the density of nearby economic activities. Findings reveal a pronounced economic duality between tourism and non-tourism businesses: tourism-oriented ventures exhibit greater income potential but higher volatility, while non-tourism operations show more consistent and stable earnings. Moreover, geographical and environmental conditions have a substantial impact on income levels, as businesses nearer to tourist zones and high-activity economic hubs generate substantially higher revenues than those in less advantageous locations. Keywords : Economic duality, Tourism area, Sajen Village